2000
DOI: 10.1021/bi000402j
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Oxidized Bacillus pasteurii Cytochrome c553 at 0.97-Å Resolution

Abstract: This article reports the first X-ray structure of the soluble form of a c-type cytochrome isolated from a Gram-positive bacterium. Bacillus pasteurii cytochrome c(553), characterized by a low reduction potential and by a low sequence homology with cytochromes from Gram-negative bacteria or eukaryotes, is a useful case study for understanding the structure-function relationships for this class of electron-transfer proteins. Diffraction data on a single crystal of cytochrome c(553) were obtained using synchrotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 68 publications
(105 reference statements)
5
60
1
Order By: Relevance
“…The results showed that we may improve the structure locally in terms of the R free factor. Moreover, we have shown [53] that refinement with ComQum-X of a medium-resolution (170 pm) crystal structure of cytochrome c 553 brings the geometry of the heme group and its ligands closer to that observed in an atomic-resolution structure (97 pm) of the same protein [54]. For example, the errors in the Fe-ligand distances are reduced from 3-9, 12, and 32 pm to 1, 0, and 2 pm (for the porphyrin, His, and methionine ligands, respectively).…”
Section: Quantum Refinement Calculationsmentioning
confidence: 65%
“…The results showed that we may improve the structure locally in terms of the R free factor. Moreover, we have shown [53] that refinement with ComQum-X of a medium-resolution (170 pm) crystal structure of cytochrome c 553 brings the geometry of the heme group and its ligands closer to that observed in an atomic-resolution structure (97 pm) of the same protein [54]. For example, the errors in the Fe-ligand distances are reduced from 3-9, 12, and 32 pm to 1, 0, and 2 pm (for the porphyrin, His, and methionine ligands, respectively).…”
Section: Quantum Refinement Calculationsmentioning
confidence: 65%
“…The heme groups are well ordered, and the structures well refined, as demonstrated by limited negative and positive electron density in the (F o ÀF c ) difference maps shown for the heme regions in Figure 3. The location and identity of iron within the heme group is corroborated by a representative 14 s anomalous difference Fourier map from the Ne c-552r structure (purple mesh in Figure 3 A) in which the signal exceeded 26 s. The overall structures are PDB (resolution) [c] B. pasteureii c-553 3.36 [18] 0.35 1C75 (0.97 ) [19] Ne c-552r 3.34 [15] 0.62 4JCG (1.63 ) Ht c-552 3.23 [20] 0.62 1YNR (2.00 ) [21] Pa c-551 3.20 [15] 0.49 351C (1.60 ) [22] Ne N64D 3.13 [15] 0.71 [a] 3ZOX (2.1 ) Horse cyt c 3.06 [15] 1.00 1HRC (1.90 ) [5] [a] Average of values for the four monomers for the monoclinic crystal form. .…”
Section: Introductionmentioning
confidence: 82%
“…Like many other cytochromes c, N. europaea c 552 and B. pasteurii c 553 have histidine (His) and methionine (Met) as ligands of the heme Fe, [31,35] as shown in Figure 1. [36,37] The 0.95 X-ray resolution of cytochrome c 553 provides the most accurate model so far available for a c-type cytochrome. [37] Cytochrome c 552 is a small (9.1 kDa) soluble protein [28,36,38,39] involved in several physiological reactions, including the reduction of the diheme cytochrome peroxidase [28] and possibly the terminal cytochrome oxidase.…”
Section: Introductionmentioning
confidence: 99%
“…[36,37] The 0.95 X-ray resolution of cytochrome c 553 provides the most accurate model so far available for a c-type cytochrome. [37] Cytochrome c 552 is a small (9.1 kDa) soluble protein [28,36,38,39] involved in several physiological reactions, including the reduction of the diheme cytochrome peroxidase [28] and possibly the terminal cytochrome oxidase. [38] In vitro cytochrome c 552 is able to oxidize the tetraheme cytochrome c 554 , the electron acceptor of the 24-heme hydroxylamine oxidase (HAO), [31,32,[38][39][40] while cytochrome c 553 (molecular weight 9.6 kDa) [33,34] is proposed to be part of the electron flow chain to a terminal oxidase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation